2003
DOI: 10.1111/j.1530-0277.2003.tb04417.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responding for Brain Stimulation Reward and Sucrose in High–Alcohol‐Drinking (HAD) and Low–Alcohol‐Drinking (LAD) Rats

Abstract: Medial forebrain bundle BSR is a powerful reinforcer in both HAD-1 and LAD-1 lines. However, BSR responding was not associated with selective breeding for alcohol preference. In contrast, selective breeding for alcohol preference was associated with sucrose consumption, especially as the amount of work increased. The lack of correspondence between BSR and sweet taste rewards in HAD-1 and LAD-1 lines may suggest important differences yet an overlapping brain reward mechanism in the control of motivated behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
11
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 47 publications
5
11
1
Order By: Relevance
“…Previous studies have demonstrated a positive association between home cage ethanol (EtOH) consumption and preference for sweet solutions in rodents (Badia-Elder et al, 2000;Kampov-Polevoy et al, 1995Overstreet et al, 1997;Stewart et al, 1998). More recently, Woods et al (2003) have extended these findings by demonstrating that across a number of reinforcement schedules, the high-alcoholdrinking (HAD) rats continue to display this positive association with the reinforcing effects of sweet, palatable solutions. Similar to rodents, human alcoholics have also been reported to display a propensity to consume sweet, palatable solutions , 1999.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Previous studies have demonstrated a positive association between home cage ethanol (EtOH) consumption and preference for sweet solutions in rodents (Badia-Elder et al, 2000;Kampov-Polevoy et al, 1995Overstreet et al, 1997;Stewart et al, 1998). More recently, Woods et al (2003) have extended these findings by demonstrating that across a number of reinforcement schedules, the high-alcoholdrinking (HAD) rats continue to display this positive association with the reinforcing effects of sweet, palatable solutions. Similar to rodents, human alcoholics have also been reported to display a propensity to consume sweet, palatable solutions , 1999.…”
mentioning
confidence: 86%
“…The computer then recorded responses made by the animal in the operant chamber and triggered an A13-65 isolated physiological stimulator (Coulbourn Instruments), which, depending on the schedule of reinforcement, delivered an electrical pulse of a given current intensity into the commu-tator through the electrode wire into the MFB. The electrical stimulation for the current study was set at 0.2-sec train of 100-Hz biphasic rectangular pulses of 1.0 msec in duration, similar to that of previous research (Lewis and June, 1990;Woods et al, 2003). Responses and reinforcements were controlled and recorded during a 21-min operant session by the Dell computer using the operant software program similar to that of Li and Huston (2002).…”
Section: Brain Stimulation Reward Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in sensitivity to or preference for salty taste have been reported in subjects with a paternal history of alcohol dependence relative to control subjects with no paternal history (Scinska et al 2001). A positive association exists between ethanol intake and sweet taste (Stewart et al 1994;Woods et al 2003) involving the gene for T1R3 (Bachmanov et al 2001(Bachmanov et al , 2002Blednov and Harris 2007;Blednov et al 2008;Blizard 2007;Brasser et al 2010;Inoue et al 2004;Lu et al 2005;Nelson et al 2001), a G protein-coupled receptor (GPCR) that combines with another GPCR (T1R2) to function as the broadly tuned, heterodimeric, sweet taste receptor T1R2ϩT1R3 Zhao et al 2003). Alcohol dependence and use also show significant association with the T2R38 gene, a marker for 6-n-propylthiouracil bitterness, and with hT2R16, a gene encoding a taste receptor for the bitter-tasting ␤-glucopyranosides (Duffy et al 2004;Hinrichs et al 2006).…”
mentioning
confidence: 99%